2017
DOI: 10.3389/fped.2017.00086
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in the Pediatric Kidney Transplant Recipient

Abstract: Hypertension after kidney transplant is a frequent occurrence in pediatric patients. It is a risk factor for graft loss and contributes to the significant burden of cardiovascular disease (CVD) in this population. The etiology of posttransplant hypertension is multifactorial including donor factors, recipient factors, medications, and lifestyle factors similar to those prevalent in the general population. Ambulatory blood pressure monitoring has emerged as the most reliable method for measuring hypertension in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 109 publications
0
28
0
1
Order By: Relevance
“…In this cohort of 249 patients who started RRT in childhood and survived into adulthood (follow-up of 25.5 years), a clear decrease in CV mortality along with strict CV management and reversal of CV risk factors was observed [30,31]. A review published in 2017 describes the under-recognised and under-treated burden of hypertension in transplant patients [37]. In addition another study has reported on contradicting guidelines and differences in policies and treatment of hypertension in Dutch paediatric transplant patients [38].…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 96%
“…In this cohort of 249 patients who started RRT in childhood and survived into adulthood (follow-up of 25.5 years), a clear decrease in CV mortality along with strict CV management and reversal of CV risk factors was observed [30,31]. A review published in 2017 describes the under-recognised and under-treated burden of hypertension in transplant patients [37]. In addition another study has reported on contradicting guidelines and differences in policies and treatment of hypertension in Dutch paediatric transplant patients [38].…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 96%
“…HTN is a frequent cause of complications in paediatric patients after kidney transplantation and represents a significant risk factor for cardiovascular diseases. [3][4][5][6] For this reason, transplanted children constitute a critical group and knowledge of new risk factors is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The development or persistence of hypertension (HTN) during the post-transplantation period is a major cardiovascular comorbidity among these patients. [3][4][5][6] It is also likely that post-transplantation HTN promotes graft loss and decreases survival due to its adverse effect on renal function. 5 Besides donor and recipient factors, the most commonly identified risk factors for post-transplantation HTN include time on dialysis, immunosuppressive therapy, and transplant renal artery stenosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been reflected by the publication of international guidelines for the optimal diagnosis and management of hypertension in children and by a growing number of review articles on the topic of childhood hypertension post-renal transplantation [1019]. …”
Section: Introductionmentioning
confidence: 99%